Existence of Neural Stem Cells in Mouse Spleen - Koichi Tomita; Hiroshi Ishikawa (The Scientific World Journal)
Pluripotent stem cells are used in regenerative medicine and exist in various internal organs. However, there are a small number of reports of neural cells or neural stem cells existing in the spleen. In this study, we sought to identify possible neural stem cells in the mouse spleen. The spleens of ICR mice were removed and small specimens were incubated in Dulbecco’s modified Eagle’s medium with Nutrient Mixture F-12 containing either 10% fetal bovine serum (FBS), 20% FBS, 10% neonate bovine serum, or 10% fetal calf serum. Neural cell medium was also used. The cultured cells were investigated for expression of the neural cell markers neuron-specific enolase (NSE) and neurofilament 150 kDa (NF-150) by immunocytochemistry. Mouse spleens were also examined by immunohistochemistry for NSE, NF-150, NF-200, peripherin, and glial fibrillary acidic protein. Cells morphologically resembling neural cells were obtained and were positive for neural cell markers. Some of the cells generated sphere-like formations, which may have been neurospheres. Cell proliferation was best in medium containing 10% FBS. Cells positive for neural markers were observed in the subcapsular and perivascular regions of the spleen. The cells were round and present in much lower numbers than in cell culture. These cells are suspected neural stem cells and would be expected to differentiate into neural cells in cell culture. This report suggests the existence of neural stem cells in the mouse spleen.